2013
DOI: 10.4103/0970-2113.110422
|View full text |Cite
|
Sign up to set email alerts
|

Level of awareness about tuberculosis in urban slums: Implications for advocacy and communication strategy planning in the National program

Abstract: Background:Tuberculosis (TB) remains as an important public health problem in India. Awareness about the disease, its diagnosis, and treatment among public will help in controlling the killer disease. This study aims at arriving at an educational diagnosis about TB in an urban poor community.Materials and Methods:A cross-sectional study was conducted in an urban slum in South India using a structured, pretested questionnaire. Domains identified were knowledge about TB, symptoms, spread, diagnosis, treatment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 1 publication
2
29
2
Order By: Relevance
“…Regarding the cost of PTB treatment, only 20% knew that TB treatment is available free of cost in government health centres, whereas this was found to be 84% in a study by Chinnakali et al, 34% in a study by Kar et al, and 48.8% in a study by Mushtaq et al 16,23,24 This emphasizes the need to strengthen the health education activities, as nearly 80% of the subjects didn"t know about the free anti-TB drugs provided by the government. Community support to the PTB patients was also found to be less as nearly half of the respondents said the villagers generally tries to avoid the PTB patients.…”
Section: Practices Related To Ptbmentioning
confidence: 67%
See 4 more Smart Citations
“…Regarding the cost of PTB treatment, only 20% knew that TB treatment is available free of cost in government health centres, whereas this was found to be 84% in a study by Chinnakali et al, 34% in a study by Kar et al, and 48.8% in a study by Mushtaq et al 16,23,24 This emphasizes the need to strengthen the health education activities, as nearly 80% of the subjects didn"t know about the free anti-TB drugs provided by the government. Community support to the PTB patients was also found to be less as nearly half of the respondents said the villagers generally tries to avoid the PTB patients.…”
Section: Practices Related To Ptbmentioning
confidence: 67%
“…Sharma et al, Chinnakali et al and Elbur et al, in their study in Delhi, Puducherry and Sudan respectively reported that 94.4%, 87% and 80.3% of the participants were aware that PTB is curable. 16,17,22 In this study, being part of a nuclear family and age ≤45 years were significantly associated with adequate PTB knowledge. Tolossa et al reported that people with high education level had increased odds of having good knowledge towards PTB.…”
Section: Knowledge Regarding Ptbmentioning
confidence: 84%
See 3 more Smart Citations